Representation of Muslim Women's Self-Image in the Miss Hijab North Sumatra Competition - Rara Ardina Khairi; Faridah Faridah (Madania: Jurnal Ilmu-Ilmu Keislaman, 2026)
This study examines how the self-image of Muslim women is represented in the Miss Hijab North Sumatra 2025 pageant, a regional Islamic beauty and talent competition held at the Raja Inal Hall of the North Sumatra Governor’s Office. The research is grounded in a constructivist paradigm and employs interpretive qualitative inquiry to understand how meaning about Muslim women’s identity is socially produced. Five informants were selected through purposive sampling based on their direct involvement in the event: three finalists, one Regional Director, and one organizing committee member. Data were generated through semi-structured in-depth interviews, non-participant observation across the series of pageant activities, and documentary analysis of official guidelines, photographs, and social-media material. Data were analysed using Braun and Clarke’s six-phase reflexive thematic analysis, while trustworthiness was established through credibility, dependability, confirmability, and transferability strategies, including triangulation and member checking. Researcher reflexivity is addressed explicitly. Guided by Stuart Hall’s constructionist theory of representation, the analysis produced four interrelated themes through which Muslim women’s self-image is constructed: (1) communicative ethics as moral performance, (2) visual modesty and the hijab as a sign of religious identity, (3) intellect and articulate reasoning, and (4) an open yet faith-anchored mindset. The findings show that the pageant operates as a representational arena in which religious, modern, and agentic femininities are negotiated rather than simply displayed. The study contributes a contextually grounded account of how Islamic feminine identity is constructed in Indonesian public space and cautions that such representation may also normalise an idealised standard of the “proper” Muslim woman.